Pengaruh Social Media, Electronic Word of Mouth, Brand Image, dan Perceived Value terhadap Purchase Intention Konsumen pada Situs Online Tokopedia - Erwin Erwin (Universitas Tarumanagara, 2022)
This study aims to determine the effect of social media, electronic word of mouth, brand image, and perceived value of purchase intention. The sampling technique in this study is nonprobability sampling by purposive sampling using a quantitative approach by distributing questionnaires to 200 respondents. The data analysis method used in this study is multiple linear regression analysis. Operational variables using the Likert scale method of validity used a computer measuring instrument that is SPSS 25.0. The results showed that social media have a significant and positive effect, electronic word of mouth has a significant and positive effect, brand image has a significant and positive effect, perceived value has a significant and positive effect on purchase intention. In this study, the perceived value is the most influences of purchase intention. Penelitian ini bertujuan untuk mengetahui pengaruh social media, electronic word of mouth, brand image, dan perceived value terhadap purchase intention. Teknik pengambilan sampel pada penelitian ini adalah nonprobability sampling dengan cara purposive sampling menggunakan pendekatan kuantitatif dengan menyebarkan kuesioner kepada 200 responden. Metode analisis data yang digunakan dalam penelitian ini adalah analisis regresi linier berganda. Variabel operasional menggunakan metode skala Likert validitas digunakan alat ukur komputer yaitu SPSS 25.0. Hasil penelitian menunjukkan bahwa social media positif signifikan, electronic word of mouth positif signifikan, brand image positif signifikan, perceived value positif signifikan terhadap purchase intention. Dalam penelitian ini, perceived value paling berpengaruh terhadap purchase intention.